Methodology to design a municipal solid waste pre-collection system. A case study. (February 2015) - Gallardo, A.; Carlos, M.; Peris, M.; Colomer, F.J.
Highlights: MSW recovery starts at homes; therefore it is important to facilitate it to people. Additionally, to optimize MSW collection a previous pre-collection must be planned. A methodology to organize pre-collection considering several factors is presented. The methodology has been verified applying it to a Spanish middle town. Abstract: The municipal solid waste (MSW) management is an important task that local governments as well as private companies must take into account to protect human health, the environment and to preserve natural resources. To design an adequate MSW management plan the first step consists in defining the waste generation and composition patterns of the town. As these patterns depend on several socio-economic factors it is advisable to organize them previously. Moreover, the waste generation and composition patterns may vary around the town and over the time. Generally, the data are not homogeneous around the city as the number of inhabitants is not constant nor it is the economic activity. Therefore, if all the information is showed in thematic maps, the final waste management decisions can be made more efficiently. The main aim of this paper is to present a structured methodology that allows local authorities or private companies who deal with MSW to design its own MSW management plan depending on the available data. According to these data, this paper proposes two ways of action: a direct way when detailed data are available and an indirect way when there is a lack of data and it is necessary to take into account bibliographic data. In any case, the amount of information needed is considerable. This paper combines the planning methodology with the Geographic Information Systems to present the final results in thematic maps that make easier to interpret them. The proposed methodology is a previous useful tool to organize the MSW collection routes including the selective collection. To verify the methodology it has been successfully applied to a Spanish town.